The Pragmatic Function of Grammatical Particles in the Light of Philology: An Analytical Study in Qur’anic Contexts - خلف, قصي محمود (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Grammatical tools are among the fundamental pillars of Arabic sentence construction, yet their study within a pragmatic framework that combines philology and semantics remains limited. This research aims to analyze the pragmatic function of grammatical tools such as waw, fa, thumma, hatta, lakin, and others, by examining their various contexts in the Qur'anic text, as the highest examples of Arabic rhetoric. The pragmatic function concerns how a tool is employed to achieve the purpose of discourse, not merely its abstract lexical or grammatical meaning. Therefore, combining philology—which focuses on the development of meaning—with pragmatics—which links language to reality and context—allows us to gain a deeper and more precise understanding of the functions of tools. The research relies on the analysis of selected Qur'anic texts, deconstructing the connotations of grammatical tools within the context, identifying their pragmatic impact, and the semantic or stylistic shifts in meaning they produce. The research also compares the meanings of tools in the Qur'anic context with their meanings in ancient Arabic usage, tracing semantic development and purposeful employment. This highlights the flexibility of language and its ability to accommodate structures in light of intentions and the discursive environment. This research hopes to fill a gap in applied studies of philology, open new horizons for researchers in the functions of tools, and establish an integrated approach between the sciences of language, text, and rhetoric.